Activation of water in the downstream of low-pressure ammonia plasma discharge. (1st June 2022) - Rathore, Vikas; Desai, Vyom; Jamnapara, Nirav I.; Nema, Sudhir Kumar
Abstract: In the present work, we study the physicochemical changes that arise in water named plasma processed water (PPW) when it is exposed to the downstream low-pressure discharge of ammonia (NH3 ) gas. Optical emission spectroscopy and voltage-current characteristics of NH3 plasma are studied to identify species formed in NH3 plasma along with plasma characterization. A three-way full factorial design of experiment is performed to study the effect of process parameters named applied voltage, post-discharge gas-water interaction time, and NH3 gas pressure on physicochemical properties of PPW. The obtained results are analyzed using analysis of variance, standardized effect estimation, regression analysis, and response surfaces. The optimum values of these properties and PPW process parameters are estimated using MATLAB fmincon solver with experimental constraints. The emission spectrum of NH3 plasma showed strong intensity N2 + lines along with weak intensity N2, NH, and N + lines. The obtained results showed the post-discharge gas-water interaction time and applied voltage had a significant impact on physicochemical properties and ammonium ions concentration in PPW. The obtained optimum value of voltage and time is 550 V and 15 min with given experimental constraints.